Correction: Clinical Classification of Cancer Cachexia: Phenotypic Correlates in Human Skeletal Muscle. - Neil Johns; Shinji Hatakeyama; Nathan A Stephens; Martin Degen; Simone Degen; Wilfried Frieauff; Christian Lambert; James A Ross; Ronenn Roubenoff; David J Glass; Carsten Jacobi; Kenneth C H Fearon; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0083618.].